Racial Differences in Incidence of Staphylococcus aureus Joint Infections in Metropolitan Atlanta, 2016–2018. (October 2020) - Overton, Rahsaan; Sefton, Samantha; Thomas, Stepy; Fridkin, Scott; Webster, Andrew; Ray, Susan
Abstract : Background: Staphylococcus aureus is the leading cause of joint infections. These infections may arise in native or prosthetic joints. Previous analysis of population-based surveillance has documented racial differences in incidence of invasive S. aureus bloodstream infections. We hypothesized that racial differences in incidence would not persist among of S. aureus joint infections. Methods: We utilized data from the Georgia Emerging Infections Program (GA EIP), which conducts CDC-funded active, population-based surveillance for iSA within the 8-county area of Atlanta. Cases were defined as residents of the surveillance area with S. aureus isolated during 2016–2018 from joint fluid or tissue, and cultures within a 30-day period after the initial culture date were considered a single case. Age- and race-specific incidence were calculated using US census data; incidence rate ratios (RR) and adjusted rate ratios (aRR) were calculated using the Mantel-Hanzel method. Results: Between 2016 and 2018, 500 iSA joint infections were identified (iMRSA, 28.2% and iMSSA, 71.8%): 34.4% occurred in black patients and 65.6% occurred in white patients. Also, 90 cases (18%) had a bloodstream infection (BSI) within 30 days of the joint infection. Incidence of iSA joint infections dropped 22% from 9.4 per 100, 000 in 2016 to 7.5 per 100, 000 in 2018 (RR, 0.79; 95% CI, 0.7–0.9). Adjusting for year, incidence was 40% lower among blacks than whites (RR, 0.6, ; 95% CI, 0.5–0.7); this finding was attributed to blacks having 60% lower incidence of iMSSA joint infections compared to whites (aRR, 0.4; 95% CI, 0.3–0.5) but similar MRSA incidence (aRR, 1.2; 95% CI, 0.8–1.6). The highest incidence was observed among whites aged >65 years with iMSSA infections (30.2 per 100, 000) (Fig. 1). Among cases with a full chart review (n = 138), surgery in the prior 90 days was uncommon (n = 42, 30.4%), and a preceding major orthopedic procedure was even more rare (n = 13, 9.4%). Antecedent therapeutic injections and arthroscopic procedures are under investigation. Conclusions: Unlike S. aureus bacteremia, where previous analysis demonstrates higher incidences among blacks predominantly due to MRSA, our data demonstrate that the incidence of S. aureus joint infections is higher in whites, predominantly due to MSSA. Investigations in differential practices regarding orthopedic illness and injury should be pursued. Funding: None Disclosures: Scott Fridkin reports that his spouse receives consulting fees from the vaccine industry.